3D carbon nanotube-mesoporous carbon sponge with short pore channels for high-power lithium-ion capacitor cathodes. (25th January 2023) - Zhao, Wenqi; Yang, Jingwen; Shang, Yuanyuan; Yang, Boyu; Han, Di; Du, Gaohui; Su, Qingmei; Ding, Shukai; Xu, Bingshe; Cao, Anyuan
Abstract: Achieving high energy storage performance at high power density is expected in lithium ion capacitors (LIC), but currently it is limited by the mismatched kinetics between capacitor-type cathodes and battery-type anodes. Herein, carbon nanotube (CNT)-mesoporous carbon (mpC) sponge is an elastic three-dimensional network and prepared by self-assembling phenol functionalized melamine-based micelles on the surface of CNTs and a carbonization process. The porous structures of the mpC layers can be tailored (key factors including the pore ordering degree, coating thickness) to investigate the effects of microstructures on electrochemical properties. Due to the densely packed ordered open mesopores with straight/short channels (13.2 nm) and high N (5.28 at%) and O (5.69 at%) doping, CNT-mpC sponge cathodes possess high specific capacitances of 142 F/g (0.1 A/g). The full carbon LICs (CNT-mpC//CNT) with pure CNT sponges as anodes can deliver a high energy density of 111.8 Wh/kg at 325 W/kg. Even at an ultrahigh power density of 32500 W/kg, our LICs still achieve a satisfactory energy density of 30.7 Wh/kg. We provide a structure design for high power LIC cathodes, and our CNT-mpC sponges are promising in other energy storage systems for high performances at high power density. Graphical abstract: CNT-mpC sponge cathodes consisting of elastic 3D networks and large amounts of densely packed ordered mesopores with short channels achieve high lithium ion capacitor performances. Image 1